2022
DOI: 10.1186/s12887-022-03412-0
|View full text |Cite
|
Sign up to set email alerts
|

Is neonatal phototherapy associated with a greater risk of childhood cancers?

Abstract: Background Neonatal phototherapy (NNPT) has long been used as an effective and relatively safe method of treating neonatal hyperbilirubinemia. Considering the subsequent evidence of long-term impacts of NNPT such as malignancies, this study was conducted to evaluate the relationship between NNPT and childhood cancers. Methods This case-control study assessed 116 children up to 4 years old with every kind of cancer referred to the Oncology departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The study results indicated that no correlation was found between neonatal phototherapy and childhood cancers. 22 Attention Deficit Hyperactivity Disorders (ADHD) or Autism Spectrum Disorder (ASD) Three studies were included that explored either ADHD or ASDs. A retrospective observational study by Wei, et al explored the adverse outcome of ADHD due to neonatal phototherapy.…”
Section: Childhood Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…The study results indicated that no correlation was found between neonatal phototherapy and childhood cancers. 22 Attention Deficit Hyperactivity Disorders (ADHD) or Autism Spectrum Disorder (ASD) Three studies were included that explored either ADHD or ASDs. A retrospective observational study by Wei, et al explored the adverse outcome of ADHD due to neonatal phototherapy.…”
Section: Childhood Cancersmentioning
confidence: 99%
“…Although two of the included studies showed significant results with increased risk of childhood cancers, 20,6 two of the studies demonstrated no increased risk. 21,22 As the role of confounding factors were not controlled in the four studies included in this scoping review, studies, future large cohorts are necessary in this regard. In addition, exploring the risk of cancer as an adverse outcome of neonatal phototherapy in a wider age range might present a clearer understanding of childhood cancers as a risk from neonatal phototherapy.…”
Section: Childhood Cancersmentioning
confidence: 99%
“…Moreover, many hypotheses have been raised about the increased risk of melanoma progression during phototherapy. [ 6 7 8 ]…”
Section: Introductionmentioning
confidence: 99%